2021
DOI: 10.4103/1735-5362.305189
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and effects of food additive dye Allura red on pepsin structure and protease activity; experimental and computational supports

Abstract: Background and purpose: Today, color additives such as Allura red (AR) are widely used in different kinds of food products. Pepsin is a globular protein that is secreted as a digestive protease from the main cells in the stomach. Because of the important role of pepsin in protein digestion and because of its importance in digestive diseases the study of the interactions of pepsin with chemical food additives is important. Experimental approach: In this study, the intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The absorption intensity of the R2G-HGG samples increases with higher R2G concentrations and there are no significant changes in the peak location. red 2G (1) 0.0, (2) 0.2, (3) 0.4, (4) 0.6, (5 These results indicated that the microenvironment around the amino acid residues in HGG remains unchanged upon the interaction with R2G and a lack of significant conformational changes in the protein structure [14]. An increase in the absorbance of HGG is due to the formation of a ground-state combination between red 2G and HGG [15].…”
Section: Resultsmentioning
confidence: 88%
“…The absorption intensity of the R2G-HGG samples increases with higher R2G concentrations and there are no significant changes in the peak location. red 2G (1) 0.0, (2) 0.2, (3) 0.4, (4) 0.6, (5 These results indicated that the microenvironment around the amino acid residues in HGG remains unchanged upon the interaction with R2G and a lack of significant conformational changes in the protein structure [14]. An increase in the absorbance of HGG is due to the formation of a ground-state combination between red 2G and HGG [15].…”
Section: Resultsmentioning
confidence: 88%
“…The present study adopted a combination of computational biochemistry and experimental engineering ( 31 32 33 ) to investigate the potential interactions of the N-terminal peptide and the resultant conformational changes. We performed proteolysis on a recombinant 604-aa isoform lacking a C-terminal peptide and simulated the molecular dynamics of its modelled dimer.…”
Section: Discussionmentioning
confidence: 99%
“…When used in conjunction with the natural dye curcumin, the synergistic effect increases the stability of the Sunset Yellow FCF-catalase complex and the inhibition of enzyme activity (Khataee et al, 2019). In contrast, the van der Waals and hydrogen bonds of Allura Red AC form a stable complex with pepsin, which increases the enzyme activity (Balaei et al, 2021). Tartrazine induced DNA damage due to high binding capacity to hydrogen acceptors (nON = 13), which suggests interference with DNA hydrogen bonds (Floriano et al, 2018).…”
Section: Computational Modelingmentioning
confidence: 99%
“…It also inhibits fibrillogenesis due to its binding to β‐lactoglobulin (Patel et al., 2019). Investigating interactions between exogenous agents and biomacromolecules, such as DNA and proteins, is essential due to the possibility of interference in body homeostasis (Balaei et al., 2021). The protein with the highest concentration in human plasma is serum albumin, which binds azo dyes (tartrazine, Sunset Yellow FCF, Allura Red AC, and carmoisine) tightly via hydrogen bonds and van der Waals forces (Masone & Chanforan, 2015; Wu et al., 2015).…”
Section: Risk Assessment Of Artificial Azo Dyesmentioning
confidence: 99%
See 1 more Smart Citation